Absolute Competence of the State Administrative Court over Onrechtmatige Overheidsdaad Disputes in Indonesia’s 2024 Election - Azzahra Fitrada (Law Research Review Quarterly, 2026)
Decision of the Jakarta State Administrative Court Numbers 133/G/TF/2024/PTUN. JKT declared that the claim against the General Election Commission was inadmissible, sparking a discussion about the absolut authoritys of the State Administrative Court (PTUN) in handling onrechtmatige overheidsdaad (OOD) cases during the electoral process. This Articles explores how the PTUN’s absolute authoritys applies to OOD cases stemming from the actions of those managing elections, centering the analysis around Decision Numbers 133/G/TF/2024/PTUN. JKT. The research employs a normative legal framework with an approach that is legislative, conceptsual, and analytical, focusing on the connections betweens Governments Administrations Law, Election Law, and associated court rules and rulings. The findings indicate that the Jakarta PTUN categorizes the subject of the lawsuit as a disagreement related to the election process, falling under the specific purview of election law, thereby negating the relevance of the OOD dispute process as outlined in Governments Administrations Law and the Supreme Court Regulation Numbers 2 of 2019. The conduct of the General Election Commission is viewed as part of the enforcement of the Constitutional Court Decision Numbers 90/PUU-XXI/2023, which is conclusive and binding, making it unsuitable for review via OOD frameworks in the PTUN. The application of the principle lex specialis derogat legi generali constrains the extent of judicial review over electoral administration activities and affects both legal certainty and the efficiency of administrative legal protection.